2016
DOI: 10.1007/978-3-319-33036-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Hearing and Hearing Aids

Abstract: Spatial hearing is a central part of everyday listening. The ability to determine the direction of a sound source is a natural and effortless skill that is only remarked on in rare or challenging circumstances, such as when a driver cannot determine the direction of the siren of a passing ambulance. But spatial hearing performance by hearing-impaired listeners is considerably degraded, and generally hearing aids do not offer any benefit.In most circumstances -excepting only if a sound source is exactly directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 92 publications
4
27
0
3
Order By: Relevance
“…within 40 minutes, with 5 minutes to reliably assess the MAA at a given azimuth. Especially with multiple real sound sources at multiple azimuths, it is a difficult test to perform (Akeroyd & Whitmer 2016). Our results confirmed that the MAA increases with increasing displacement from the forward direction to the sides (Mills 1958).…”
Section: Sound Source Discriminationsupporting
confidence: 75%
“…within 40 minutes, with 5 minutes to reliably assess the MAA at a given azimuth. Especially with multiple real sound sources at multiple azimuths, it is a difficult test to perform (Akeroyd & Whitmer 2016). Our results confirmed that the MAA increases with increasing displacement from the forward direction to the sides (Mills 1958).…”
Section: Sound Source Discriminationsupporting
confidence: 75%
“…For the time-consuming MAA, we used a robot-supported, automated test procedure that acquired free-field MAAs in the full azimuthal plane at every 45 • position (i.e., 8 tested directions in total) within 40 minutes, with 5 minutes to reliably assess the MAA at a given azimuth. Especially with multiple real sound sources at multiple azimuths, it is a difficult test to perform (Akeroyd & Whitmer 2016). Our results confirmed that the MAA increases with increasing displacement from the forward direction to the sides (Mills 1958).…”
Section: Sound Source Discriminationsupporting
confidence: 75%
“…It has been shown that listeners with hearing loss are far more prone to front-back confusions than are normal hearing listeners (Akeroyd & Whitmer, 2016; Vaillancourt, Laroche, Giguère, Beaulieu, & Legault, 2011; Van den Bogaert, Carette, & Wouters, 2011). While there is substantial inter-subject variability, the overwhelming trend is that wearing hearing aids offers little-to-no improvement in distinguishing front from back and can even make matters worse with hearing aids placed behind the ear (Best et al, 2010; Van den Bogaert et al, 2011).…”
Section: Introductionmentioning
confidence: 99%